2015
DOI: 10.2147/jbm.s82411
|View full text |Cite
|
Sign up to set email alerts
|

Rate and predictors of low serum ferritin levels among healthy parturient women in Enugu, Nigeria

Abstract: BackgroundLow serum ferritin levels signify low iron stores and this could predispose to iron deficiency anemia.ObjectiveTo determine the rate and predictors of low serum ferritin levels during the puerperium in Enugu, Southeast Nigeria.Study designA hospital-based prospective longitudinal study involving parturient women who delivered singleton fetuses at term. Venous blood samples were collected to determine the serum ferritin concentration at 48 hours and 6 weeks postpartum. Data analysis involved descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…There was however, a higher maternal Ferritin level, one of the secondary outcomes, in the intervention group suggesting there was a replenishment of iron stores with high energy biscuits. It is widely accepted that serum ferritin remains the best indicator of iron stores in the absence of inflammation [17] and poor compliance to iron supplements during pregnancy are associated anaemia in puerperium even [18]. Though we cannot exclude inflammation as a contributor to the difference, there was no clinical reason to suspect this.…”
Section: Discussionmentioning
confidence: 76%
“…There was however, a higher maternal Ferritin level, one of the secondary outcomes, in the intervention group suggesting there was a replenishment of iron stores with high energy biscuits. It is widely accepted that serum ferritin remains the best indicator of iron stores in the absence of inflammation [17] and poor compliance to iron supplements during pregnancy are associated anaemia in puerperium even [18]. Though we cannot exclude inflammation as a contributor to the difference, there was no clinical reason to suspect this.…”
Section: Discussionmentioning
confidence: 76%
“…Two recent studies from our center had shown that the level of anemia at 6 weeks postpartum was high among low risk parturients and that iron-deficiency anemia contributed significantly to this finding 16,30. From anecdotal evidence, it would appear that considerable uncertainty about patient’s compliance with daily oral iron postdelivery existed and that noncompliance with oral therapy could be contributing to this high level of puerperal anemia.…”
Section: Discussionmentioning
confidence: 95%
“…Two recent studies from our center had shown that the level of anemia at 6 weeks postpartum was high among low risk parturients and that iron-deficiency anemia contributed significantly to this finding. 16 , 30 From anecdotal evidence, it would appear that considerable uncertainty about patient’s compliance with daily oral iron postdelivery existed and that noncompliance with oral therapy could be contributing to this high level of puerperal anemia. In order to address the problem of compliance with oral iron following delivery, we conducted this study to determine if a single total dose of intravenous iron given to parturients 48 hours after delivery would be as effective as the current practice of daily oral doses of ferric iron given for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is associated with physiological changes that results in increased plasma volume and red blood cells and decreased concentration of micronutrients like (iron, folic acid and vitamin B12) [1] . Physiological alterations in plasma volume and red cell mass diminish the reliability of Hb estimation or determination of hematocrit, due to increase demand of iron as a result of fetal and placental growth as well as expansion of blood volume [2] . It is well known fact that hemoglobin concentration falls during pregnancy principally as a result of hemodilution.…”
Section: Introductionmentioning
confidence: 99%